2014
DOI: 10.1007/s10611-014-9536-4
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance as casework: supervising domestic violence defendants with GPS technology

Abstract: Academic discussion about surveillance tends to emphasize its proliferation, ubiquity, and impact on society, while neglecting to consider the continued relevance of traditional approaches to human supervision, an oversight insofar as surveillance is organized through practices embedded in justice system-based casework. Drawing from a multi-site study of pretrial personnel utilizing global positioning systems (GPS) technology for domestic violence cases in the U.S., a comparative analysis is offered to illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 45 publications
(99 reference statements)
1
30
0
Order By: Relevance
“…By contrast, research in the United States-where EM has been adopted by probation and community corrections-has found that officers who use EM in DV pretrial programs have greater latitude to mix hard and soft technologies (Ibarra, 2005;Ibarra et al, 2014), approximating the case assessment and intervention model more fully. 6 Trained as specialists in DV cases, officers use insights gleaned from hard technologies (e.g., monitoring logs, urine screens, text messages) to pursue leads and gather additional information that can organize the "working of the case" in particular directions (e.g., assistance, law enforcement), as set by the agency (Ibarra, 2005;Ibarra et al, 2014).…”
Section: Penological Driftmentioning
confidence: 98%
See 2 more Smart Citations
“…By contrast, research in the United States-where EM has been adopted by probation and community corrections-has found that officers who use EM in DV pretrial programs have greater latitude to mix hard and soft technologies (Ibarra, 2005;Ibarra et al, 2014), approximating the case assessment and intervention model more fully. 6 Trained as specialists in DV cases, officers use insights gleaned from hard technologies (e.g., monitoring logs, urine screens, text messages) to pursue leads and gather additional information that can organize the "working of the case" in particular directions (e.g., assistance, law enforcement), as set by the agency (Ibarra, 2005;Ibarra et al, 2014).…”
Section: Penological Driftmentioning
confidence: 98%
“…Research conducted there demonstrates that EM officers do not utilize the information that they acquire to engage in the kind of case supervision associated with probation, in either a "treatment" or "crime control" sense: they do not have the requisite training or direction, but are instead evaluated relative to profitdriven benchmarks that limit the time officers can spend on a given case and hence result in cursory follow-up in the field (Hucklesby, 2011;Jones, 2005;Paterson, 2007). By contrast, research in the United States-where EM has been adopted by probation and community corrections-has found that officers who use EM in DV pretrial programs have greater latitude to mix hard and soft technologies (Ibarra, 2005;Ibarra et al, 2014), approximating the case assessment and intervention model more fully. 6 Trained as specialists in DV cases, officers use insights gleaned from hard technologies (e.g., monitoring logs, urine screens, text messages) to pursue leads and gather additional information that can organize the "working of the case" in particular directions (e.g., assistance, law enforcement), as set by the agency (Ibarra, 2005;Ibarra et al, 2014).…”
Section: Penological Driftmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to pair police with community correctional agencies continue to grow in popularity in the United States (Murphy, 2008) and are representative of a movement toward maintaining surveillance on high risk populations in the criminal justice system as a whole (Cotter and De Lint, 2009;Ibarra et al, 2014;Jannetta and Lachman, 2011;McGarrell et al, 2005;Paterson and Clamp, 2014). These partnerships have the potential to enhance public safety by adding focused deterrence and an additional layer of monitoring to known offenders under supervision, interrupting criminal behaviors through timely responses, and addressing locally specified crime problems through intelligence sharing (Jannetta andLachman, 2011: McGarrell et al, 2005;Murphy, 2008).…”
Section: Police As Interagency Partnersmentioning
confidence: 99%
“…Study participants have provided unique perspectives regarding their experiences with police and their expectations of police roles in a pretrial setting where GPS supervision is used to monitor high-risk defendants. In an era where the monitoring of offenders with GPS technology has rapidly expanded across the United States and has gained momentum in the United Kingdom, Spain, and Latin America (Cotter and De Lint, 2009;Ibarra et al, 2014;Paterson and Clamp, 2014), these perspectives generate insights as to how police can be leveraged to create new, or enhance existing, criminal justice responses to IPV/DV offenses. This study seeks to broaden knowledge on perceived police roles and responses in managing IPV/DV crimes, contribute to ongoing discussions of best practice for police and criminal justice system processing, and advance an agenda for future research focused on the extended roles of the police during and after IPV/DV encounters.…”
Section: Introductionmentioning
confidence: 99%